Endoplasmic reticulum stress in hepatic steatosis and inflammatory bowel diseases - Guo, Beichu; Li, Zihai (Frontiers in Genetics, 2014)
As an adaptive response to the overloading with misfolded proteins in the endoplasmic reticulum (ER), ER stress plays critical roles in maintaining protein homeostasis in the secretory pathway to avoid damage to the host. Such a conserved mechanism is accomplished through three well-orchestrated pathways known collectively as unfolded protein response (UPR). Persistent and pathological ER stress has been implicated in a variety of diseases in metabolic, inflammatory and malignant conditions. Furthermore, ER stress is directly linked with inflammation through UPR pathways, which modulate transcriptional programs to induce the expression of inflammatory genes. Importantly, the inflammation induced by ER stress is directly responsible for the pathogenesis of metabolic and inflammatory diseases. In this review, we will discuss the potential signaling pathways connecting ER stress with inflammation. We will also depict the interplay between ER stress and inflammation in the pathogenesis of hepatic steatosis, inflammatory bowel diseases and colitis-associated colon cancer.